PENGUATAN KEMAMPUAN NUMERASI MAHASISWA TEKNIK SIPIL MELALUI LESSON STUDY DENGAN PENERAPAN PEMBELAJARAN BERBASIS MASALAH - Afniria Pakpahan; Nurhasana Siregar; Wirna Arifitriana (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2023)
Numerical ability is one of the competencies that must be possessed by early-level students. For this reason, it is necessary to study the optimal effort to strengthen numeracy skills by conducting lesson study activities by applying problem-based learning. This research is a pre-experimental research with a one-class research sample, data collection is carried out by giving a pretest and posttest of numeracy skills in the form of essay test questions as many as five questions. The data analysis used is descriptive analysis by calculating the average and calculating the percentage, then using the calculation of the N-Gain score. Students' numeracy skills increased after lesson study was carried out by applying problem-based learning, namely from not being able to being able to with good abilities with a score of each ability in communication, mathematics, choosing strategies to solve problems and using mathematical tools was 1.49; 1.29; 1.02; 0.63 (pretest) and 2.73; 2.60; 2.44; 2.36 (posttest). The percentage of achievement of student numeracy abilities as a whole is >85%. The comparison of the mean scores of the pretest and posttest N-Gain obtained 0.75 with a good category. the application of problem-based learning with the lesson study system has an impact on strengthening the numeracy skills of Civil Engineering students.